The Application of Entrepreneurial Elements in Mathematics Teaching: Challenges for Primary School Mathematics Teachers - Mahmud, Muhammad Sofwan; Maat, Siti Mistima; Rosli, Roslinda; Sulaiman, Nur Ainil; Mohamed, Shahrul Badriyah (Frontiers in Psychology, 2022)
The entrepreneurial element is one of the aspects emphasised in the primary school mathematics education curriculum in Malaysia. However, previous studies have found that application of entrepreneurial elements in mathematics teaching is still lacking. This study was therefore conducted to identify the real challenges that mathematics teachers face in applying the entrepreneurial element in mathematics teaching. This study is qualitative case study which involved six primary school mathematics teachers. Semi-structured interviews, observation, document analysis and field notes were used for the data collection process in this study. The data obtained was analysed using the constant comparative analysis method to determine themes and sub-themes. The findings were that a teacher’s knowledge, teaching style, limited time of teaching, and attitudes, and in-service courses and training are among the identified challenges in applying entrepreneurial elements in mathematics teaching. This study expands knowledge and the literature on the challenges faced by school mathematics teachers in applying entrepreneurial elements in mathematics teaching. Various initiatives need to be taken to ensure that all the challenges can be overcome, and ultimately enable the entrepreneurial elements to be applied to students more widely.